Estudo da composição de leite de vacas ½ sangue holandês/Montbéliarde comparado com leite de vacas holandesas - Pivetta, Franciele Pozzebon (2016)
From a nutritional point of view, milk is a food whose components are in the proper ratio, and that contains most of the essential nutrients to the feeding of the species to which it is intended. Man has taken advantage of the nutritional properties of milk to use it in their own power, especially from higher commercial value species, due to its high degree of specialization in dairy production. To serve this purpose, the milk must meet certain quality criteria that address complex and diverse aspects. This study aimed to characterize the dairy cows ½ Holstein/Montbeliarde through physical-chemical evaluation (acidity, density, protein, fat, total solids, nonfat dry extract), daily production and lipid profile during a period of lactation (ten months) compared to milk from Holstein cows, aimed also develop cheese Minas Frescal made with milk from both animals as well as evaluating the cheese, whey and milk used for the preparation (moisture, density, fat, protein , ash, fat and carbohydrates), income, numbers of transition and sensory analysis (emotional acceptance tests, preference and purchase intent). Their results showed a significant difference between the animal milk ½ Holstein/Montbeliarde and Holstein animal milk for density, fat, protein, total solids, nonfat dry extract and daily production, lipid profile analysis there was significant difference between treatments. In the analysis of cheeses, the yield was higher for cheese made with cow milk ½ Holstein/Montbeliarde, fat was the element with the highest percentage of transition and generally the cheeses were sensory acceptance.